What are the Differences between Group and Individual Modeling when Learning BPMN? - Paschoal, Leo Natan; Santos, Italo de Oliveira; Mori, Allan Victor; Conte, Tayana Uchôa; Souza, Simone do Rocio Senger de (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2020)
Models that describe the business processes adopted by an organization are widely used in industry, especially in consultancy services for improvements or new solutions based on system information. Learning business process modeling (e.g., Business Process Modeling Notation - BPMN) is a fundamental skill for Information System undergraduate students to master. Nevertheless, learning how to model BPMN is not a trivial task for students. Some studies have highlighted the importance of providing opportunities for students to learn how to develop the "AS IS"and "TO-BE"models in groups. Group modeling aims to contribute to the student’s learning process by providing opportunities for discussion and reflection with their classmates. Although there are previous studies that mention initiatives in which BPMN activities are performed in teams or groups, there is still no consolidated knowledge as to whether group modeling is better than individual modeling. This paper presents an experimental study designed to verify whether there are differences between modeling business processes in groups or individually. The experimental study was conducted with undergraduate students in Information Systems courses, evaluating the quality of the BPMN ("AS IS"and "TO-BE") models produced by these students in terms of completeness and correctness. Unlike expected, in most cases group modeling showed results similar to those of individual modeling. These results and insights motivate future analysis of how students can best learn business process modeling technique.